Analysis of Non-Pharmacological Factors Influencing the Success of Hypertension Therapy in Productive Age Patient - Adzkiya Nabila Humaira (Institute of Accounting Research and Novation (IARN), 2025)
Hypertension is a major public health problem that increasingly affects productive-age populations and contributes to long-term cardiovascular risk, reduced work productivity, and increased healthcare burden. Although pharmacological therapy remains central to hypertension management, optimal blood pressure control cannot be achieved without addressing non-pharmacological factors related to lifestyle, behavior, and psychosocial conditions. This study aimed to analyze non-pharmacological factors influencing the success of hypertension therapy among productive-age patients. A quantitative analytical study with a cross-sectional design was conducted among hypertensive patients aged 18–59 years who were undergoing hypertension management. Data were collected using structured questionnaires to assess lifestyle behaviors, psychosocial factors, and self-management practices, alongside standardized blood pressure measurements. Descriptive statistics, bivariate analysis, and multivariate logistic regression were applied to identify independent non-pharmacological predictors of therapy success while controlling for potential confounding variables. The results indicated that a considerable proportion of productive-age patients had not achieved optimal blood pressure control. Multivariate analysis showed that adherence to healthy dietary practices, regular physical activity, effective stress management, adequate sleep, and strong social support were significant positive predictors of successful hypertension therapy. In contrast, smoking behavior, sedentary lifestyle, and high work-related stress were negatively associated with controlled blood pressure. In conclusion, the success of hypertension therapy among productive-age patients is strongly influenced by non-pharmacological factors in addition to pharmacological treatment. Integrating lifestyle modification, psychosocial support, and self-management strategies into routine hypertension care particularly through nursing, health promotion, and workplace-based interventions is essential to improve blood pressure control and reduce the long-term burden of hypertension in productive-age populations.